Meningkatkan pengetahuan tentang kebersihan diri saat menstruasi melalui edukasi berbasis pondok pesantren - Lestari, Juwita; Aryastuti, Nurul (JOURNAL OF Community Health Issues, 2025)
Background: Menstrual hygiene can increase the risk of sexually transmitted infections and reduce the quality of life of adolescent girls in Islamic boarding schools. Purpose: To increase awareness of personal hygiene during menstruation. Method: A knowledge questionnaire was completed to assess female students' knowledge of personal hygiene during menstruation. It was revealed that some students still lacked understanding of proper menstrual hygiene. Education was conducted using posters and interactive discussions on how to maintain hygiene during menstruation and how to properly dispose of sanitary napkins. Results: After the education, students' knowledge began to improve, as evidenced by their increased knowledge and understanding during lengthy discussions. Conclusion: Islamic boarding school-based education is an effective way to increase knowledge about menstruation while preserving the environment and culture of Islamic boarding schools.   Keywords: Islamic Boarding School; Knowledge; Menstruation; Personal Hygiene.   Pendahuluan: Kebersihan menstruasi dapat meningkatkan risiko infeksi menular seksual dan menurunkan kualitas hidup remaja putri di pesantren. Tujuan: Untuk meningkatkan kesadaran akan kebersihan diri saat menstruasi. Metode: Diawali dengan pengisian kuesioner pengetahuan untuk melihat pengetahuan santriwati tentang kebersihan diri saat menstruasi, terlihat bahwa masih ada yang belum memahami tentang cara merawat kebersihan diri saat menstruasi yang baik.​ Edukasi dilakukan dengan menggunakan media poster dan diskusi interaktif tentang cara menjaga kebersihan saat menstruasi dan cara membuang sampah pembalut yang baik. Hasil: Setelah dilakukan edukasi Hasil menunjukkan pengetahuan siswa mulai mengalami peningkatan, terlihat dari rasa tahu dan pemahaman siswa saat berdiskusi cukup lama. Simpulan: Edukasi berbasis pondok pesantren merupakan salah satu cara efektif untuk meningkatkan pengetahuan tentang menstruasi sekaligus menjaga kelestarian lingkungan dan budaya pesantren.   Kata Kunci: Kebersihan Diri; Menstruasi; Pengetahuan; Pondok Pesantren.